Nearly Aberration-Free Multiphoton Polymerization into Thick Photoresist Layers - Horváth Bence (MICROMACHINES, 2017)
In the era of lab-on-chip (LOC) devices, two-photon polymerization (TPP) is gaining more and more interest due to its capability of producing micrometer-sized 3D structures. With TPP, one may integrate functional structures into microfluidic systems by polymerizing them directly inside microchannels. When the feature of sub-micrometer size is a requirement, it is necessary to use high numerical aperture (NA) oil-immersion objectives that are optimized to work close to the glass substrate-photoresist interface. Further away from the substrate, that is, a few tens of micrometers into the photoresist, the focused beam undergoes focal spot elongation and focal position shift. These effects may eventually reduce the quality of the polymerized structures; therefore, it is desirable to eliminate them. We introduce a method that can highly improve the quality of structures polymerized tens of micrometers away from the substrate-photoresist interface by an oil-immersion, high NA objective. A spatial light-modulator is used to pre-compensate the phase-front distortion introduced by the interfacial refractive index jump on the strongly converging beam.